Unraveling the supply-service relationship between high-speed railway and conventional railway: A temporal perspective - Zhang, Guangxia; Liu, Yanfang; Jing, Ying; Chen, Huiting; Wang, Yiheng; Wang, Zhengyu (Frontiers in Environmental Science, 2023)
With the rapid development of high-speed railway (HSR), many scholars have studied the competition between HSR and aviation or inter-city coach, but few studies have discussed the supply-service relationship within the railway system. This paper explores the competition and cooperation between HSR and conventional railway (CR) at the city-pair level of 39 core cities in China from the temporal perspective. Comprehensive considering the departure time and arrival time between city pairs as the representation of train service quality, we find that the proportion of superior quality service of high-speed train (HST) is far higher than that of conventional train (CT). However, the time slots representing the competition degree show that CR with fewer superior quality trains is easier to be replaced than HSR. The supply-service relationships of the railway system indicate that HSR has become the main transportation mode between core cities, and the CR, as an auxiliary transportation, shows a certain complementary effect in the temporal perspective. Spatially, HSR and CR services are more likely to generate temporal competition on the mainline, but temporal complementarity between city pairs on non-arterial lines. This study can provide inspiration for regional spatial planning by better understanding the operation strategy of railway passenger transport system.